Implementasi Pemberdayaan Kolaboratif Terkait Kebijakan Perhutanan Sosial Pada Pulau-Pulau Kecil di Pulau Hiri - B, Sabaruddin; Tamrin, Mahdi; Kamaluddin, Abdul Kadir; Baguna, Firlawanti Lestari; Tamnge, Fadila (Program Studi Kehutanan, Universitas Khairun, 2025)
Forests play a crucial role in maintaining the balance of the ecosystem and supporting human life. However, major challenges such as rapid deforestation and unsustainable resource utilization threaten the sustainability of forest functions. This study explores the implementation of social forestry policies in Pulau Hiri District, Ternate City, North Maluku Province, as a solution to overcome this problem. Through Community Service (PKM) activities involving students and lecturers from the Forestry Study Program of Khairun University, socialization and training on sustainable forest management, especially in clove oil refining, were carried out. The results of this activity show an increase in public understanding of social forestry and the implementation of sustainable agroforestry systems. Thus, this research emphasizes the importance of collaboration between various parties in empowering communities and preserving forests, in order to achieve sustainable welfare and environmental protection.